6DIVE: 6 Degrees-of-Freedom Immersive Video Editor - Griffin, Ruairi; Langlotz, Tobias; Zollmann, Stefanie (Frontiers in Virtual Reality, 2021)
Editing 6DoF videos using standard video editing tools is challenging, especially for non-expert users. There is a large gap between the 2D interface used for traditional video editing and the immersive VR environment used for replay. In this paper, we present 6DIVE, a 6 degrees-of-freedom (DoF) immersive video editor. 6DIVE allows users to edit these 6DoF videos directly in an immersive VR environment. In this work, we explored options for a timeline representation as well as UI placement suitable for immersive video editing. We used our prototypical implementation of an immersive video editor to conduct a user study to analyze the feasibility and usability of immersive 6DoF editing. We compared 6DIVE to a desktop-based implementation of a VR video editor. Our initial results suggest that 6DIVE allows even non-expert users to perform basic editing operations on videos in VR. While we did not find any statistically significant differences for the workload between the VR and the desktop interface, we found a statistically significant difference in user preference, with a preference for the VR interface. We also found higher ratings for the user experience metrics in VR captured by the user experience questionnaire.